Saídas e retornos ao lar parental sob o olhar da diferenciação - Lourenço, Cinthia de Carvalho (2012)
In the context of Post-Modernity society has been facing numerous changes in the families shapes. One of them is the attempt of a young adult to leave and, later, return to the parental home. In order to understand what motivates such phenomenon, a qualitative research including case study was made. The theoretical assumptions underlining this paper are researches and literature discussing the subject, as well as authors of the Family Systems Theory, but aiming for a differentiated interpretation. The analysis of the interviews was conducted under two guidelines: differentiation and general aspects of the exits and returns of the son to the parents house, a summary about the family s life history and a genogram. The research provided data showing the cycle of leaving and coming back to parent s house is related to certain aspects of a family dynamics, to the relationship between parents and sons and social and economic characteristics of our contemporary reality. It was noted there are few researches about the subject, especially related to its psychological aspects. Data found in current literature refers mainly about the prolonged stay of young adult with his/her parents. Therefore, it is necessary to further research on the topic in question